Emerging Trends in Chemical Sciences (Springer International Publishing, 2018)
Thirty carefully selected, peer-reviewed contributions from the International Conference on Pure and Applied Chemistry (ICPAC 2016) are featured in this edited book of proceedings. ICPAC 2016, a biennial meeting, was held in Mauritius in July 2016. The chapters in this book reflect a wide range of fundamental and applied research in the chemical sciences and interdisciplinary subjects. This is a unique collection of full research papers as well as reviews.